Reading Comprehension Difficulties Encountered by English Students of Islamic University of Riau - Estika Satriani (UIR Press, 2018)
The aim of this research is to find out the difficulties of reading comprehension faced by the first semester of students in FKIP UIR Pekanbaru. Kualitative research design in case study used in this research by using the instruments were questionnaire and interview guide. Based on the results of analyzing data from the questionnaire and interview, the reseacher found most of students’ difficulties in reading comprehension because they have no motivation in reading habit, they read a little or nothing. It is considered to be a problem for the students to comprehend a reading text. Another students’ difficulties in reading comprehension was the low reading skill. The students complained about the fact that they found, they need to study hard to remember the information they just read. They also need much time to read the text to overcome their problem. Too difficult reading material is also one of students problem in understanding the reading text. The material of reading is unfamiliar for them and grammatical complexity is also a reason why the students failed to comprehend the text correctly. The sentences in reading text too long or having complicated sentences. Related with these problem, new words and long texts are seen by the students as a major obstacle to comprehend a reading text.